The potential of synthetic indolylquinoline derivatives for Aβ aggregation reduction by chemical chaperone activity. (February 2016) - Chang, Kuo-Hsuan; Chiu, Ya-Jen; Chen, Shu-Ling; Huang, Chen-Hsiang; Lin, Chih-Hsin; Lin, Te-Hsien; Lee, Chi-Mei; Ramesh, Chintakunta; Wu, Chung-Hsin; Huang, Chin-Chang; Fung, Hon-Chung; Chen, Yi-Chun; et al.
Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia associated with progressive cognitive decline and memory loss. Extracellular β-amyloid (Aβ) is a major constituent of senile plaques, one of the pathological hallmarks of AD. Aβ deposition causes neuronal death via a number of possible mechanisms such as increasing oxidative stress. Therefore therapeutic approaches to identify novel Aβ aggregate reducers could be effective for AD treatment. Using a Trx-His-Aβ biochemical assay, we screened 11 synthetic indolylquinoline compounds, and found NC009-1, -2, -6 and -7 displaying potential to reduce Aβ aggregation. Treating Tet-On Aβ-GFP 293 cells with these compounds reduced Aβ aggregation and reactive oxygen species. These compounds also promoted neurite outgrowth in Tet-On Aβ-GFP SH-SY5Y cells. Furthermore, treatment with above compounds improved neuronal cell viability, neurite outgrowth, and synaptophysin expression level in mouse hippocampal primary culture under oligomeric Aβ-induced cytotoxicity. Moreover, the tested NC009-1 significantly ameliorated Aβ-induced inhibition of hippocampal long-term potentiation in mouse hippocampal slices. Our results demonstrate how synthetic indolylquinoline compounds are likely to work as chemical chaperones in Aβ-aggregation reduction and neuroprotection, providing insight into the possible applications of indolylquinoline compounds in AD treatment. Highlights: Indolylquinoline compounds work as chemical chaperones in Aβ-aggregation reduction. Indolylquinolines suppress ROS and promote neurite outgrowth in Aβ-expressing cells. Indolylquinolines provide neuroprotection in Aβ-treated mouse hippocampal cells. Indolylquinolines ameliorate Aβ-induced inhibition of LTP in mouse hippocampal slices.